Fabrication of a Large-area-patterned Monolayer of Polytetrafluoroethylene Nanoparticles by Surface Charge Induced Colloidal deposition. Issue 1663 (9th April 2014) - Du, Chuan; Wang, Jiadao; Chen, Darong
ABSTRACT: A facile and novel method of fabricating large-area-patterned monolayer of polytetrafluoroethylene(PTFE) nanoparticles was achieved using surface charge induced colloidal deposition. Chemical processes of amination and hydroxylation were used to make the silicon substrates positively and negatively charged, respectively, while the PTFE colloidal nanoparticles were anisotropic and negatively charged. After colloidal deposition, an ordered monolayer with microholes was formed on the amination surface, while an island-like monolayer was achieved on the hydroxylation surface. Both of the two kinds of monolayers were as large as 1.5 square centimeters. It is worth pointing out that these large-area-patterned monolayers were fabricated without any templates and the whole process only took several hours. The formation mechanism of the different structures can be generally attributed to the cooperation and competition of three-body, two-body and particle-wall interactions. It is believed that the interesting patterned monolayer formation mechanism, high production efficiency, good adaptability and quality will make this novel method attractive.